2020
DOI: 10.1108/srj-10-2019-0360
|View full text |Cite
|
Sign up to set email alerts
|

How can scientists and engineers contribute to organisational sustainability reform?

Abstract: Purpose This paper aims to explore how research and development (R&D) scientists and engineers can contribute to sustainability initiatives in their organisations. Design/methodology/approach This paper uses a critical case study methodology, focussed on a large Vietnamese company in which business leaders sought to engage R&D scientists and engineers in sustainability initiatives focussed on eco-innovation and eco-efficiency. Bourdieu’s theoretical lens of habitus, capitals and field facilitates a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Habitus was defined as a “system of durable, transposable dispositions” (Bourdieu 1990 , p. 87), or in other words, habitus is a consequence of tradition, the continuity, and constancy of behaviors, which are assured over time. Bourdieu ( 1990 , p. 88) highlighted the dependability of habitus as follows: “habitus tends to ensure its own constancy and its defense against change through the selection it makes with new information by rejecting information capable of calling into question its accumulated information.” However, Bourdieu ( 1990 , p. 88) denies that habitus allowed “the free production of all the thoughts, perceptions and actions inherent in the particular conditions of its production, and only those.” Rather, habitus constructs a middle field between the agent’s rights and the artificial determinism of activities (Hoang et al 2020 ).…”
Section: Methodology Theoretical Framework and Research Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitus was defined as a “system of durable, transposable dispositions” (Bourdieu 1990 , p. 87), or in other words, habitus is a consequence of tradition, the continuity, and constancy of behaviors, which are assured over time. Bourdieu ( 1990 , p. 88) highlighted the dependability of habitus as follows: “habitus tends to ensure its own constancy and its defense against change through the selection it makes with new information by rejecting information capable of calling into question its accumulated information.” However, Bourdieu ( 1990 , p. 88) denies that habitus allowed “the free production of all the thoughts, perceptions and actions inherent in the particular conditions of its production, and only those.” Rather, habitus constructs a middle field between the agent’s rights and the artificial determinism of activities (Hoang et al 2020 ).…”
Section: Methodology Theoretical Framework and Research Settingsmentioning
confidence: 99%
“…However, Bourdieu (1990, p. 88) denies that habitus allowed "the free production of all the thoughts, perceptions and actions inherent in the particular conditions of its production, and only those." Rather, habitus constructs a middle field between the agent's rights and the artificial determinism of activities (Hoang et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Although CSR activities are mainly associated with organisations in developed countries, different concepts of CSR have recently emerged in the developing world. However, the comprehensive understanding of the long-term benefits of CSR is still low and in its infancy, owing to the fact that most of the businesses in developing countries are small- and medium-sized enterprises (SMEs) and the CSR agenda and CSR practices of these firms were to either improve corporate reputation, attract attention from potential investors or satisfy regulatory requirements (Jamali and Neville, 2011; Jamali et al , 2017; Hoang et al , 2020a). In the same vein, Nguyen et al (2019) examined the optimal level of CSR, as demonstrated by businesses in developing countries and concluded that SMEs could promote sustainability, increase new business opportunities and innovations through CSR activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bourdieu’s (1986) theoretical perspective placed the activities shaped by an individual in an organisation at the centre of the theoretical framework. Organisation members such as managers or entrepreneurs drive many different practices including social responsibility initiatives such as giving donations, environmental technologies adoption of cleaner production (Azmat, 2010; Hoang et al , 2020a; Hoang et al , 2020b). These actions have been accomplished in the social field of organisation, where professions compete for different capitals of “social,” “cultural” and “economic” (Bourdieu, 1986, p. 249).…”
Section: Theoretical Framingmentioning
confidence: 99%
See 1 more Smart Citation